PENGARUH PAJAK HOTEL PAJAK RESTORAN DAN PAJAK REKLAME SERTA PAJAK PENERANGAN JALAN TERHADAP PENDAPATAN ASLI DAERAH KOTA KUPANG TAHUN 2013-2018 - Maria Purnama; Herni Sunarya; Fitriningsi Amalo (PROGRAM STUDI AKUNTANSI - UNIVERSITAS MUHAMMADIYAH KUPANG, 2021)
His study aims to determine: the effect of hotel tax, restaurant tax and advertisement taxand street lighting tax on local revenue in Kupang city in 2013-2018. In this study theauthor uses quantitative data using secondary data, the data collection methods in thisstudy are documents and library methods. The analytical technique used in this study isthe classical assumption test and multiple linear regression. The results of this first studyindicate that hotel tax has a significant effect on local revenue with a t count of -1714,309with a significance of 0.000 < 0.05, the second restaurant tax has a significant effect onlocal revenue in Kupang with a t count of 27,299 with a significance of 0.23. <0.05, thethree advertisement taxes have a significant effect on local revenue in Kupang with tcount -1991,213 with a significance of 0.001 < 0.05, the four street lighting taxes have asignificant effect on local revenue in Kupang with t count 1501.454 with significance0.000 < 0.05; Simultaneously hotel tax, restaurant tax, and advertisement tax and streetlighting tax have an effect on local revenue with F count 6148802 with a significance of0.000 < 0.005. Based on the results of this study, partially and simultaneously hotel tax,restaurant tax and advertisement tax and street lighting tax affect the local revenue ofKupang city in 2013-2018 its revenue increases. Suggestions from the BPD to maintainand try to increase hotel tax revenues, restaurant taxes, advertisement taxes and streetlighting taxes can optimize and pay attention to developments in the city of Kupang suchas street lighting.